DATE EXTRACT SUPPLEMENTATION IN RINGER LACTATE-EGG YOLK EXTENDER ON POST-THAWING QUALITY OF PELUNG CHICKEN SPERMATOZOA - Nu'man - Hidayat; Ismoyowati Ismoyowati; Elly Tugiyanti; Imam Suswoyo; Rosidi Rosidi; Ibnu Hari Sulistyawan; Aras Prasetyo Nugroho (Universitas Syiah Kuala, 2022)
The research purpose was to evaluate the influence of date extract supplementation in lactate ringer-egg yolk extender with 0.025% sodium dodecyl sulfate (LREYS) on post-thawing quality of Pelung chicken spermatozoa. Completely randomized design with 5 treatments and 4 replications was used in this study. Semen was collected from three Pelung chickens once in three days using the dorsal-abdominal massage method. Semen was divided into 5 treatment groups of date extract supplementation that were 0% as control (LREYSDE0), 0.5% (LREYSDE1), 1% (LREYSDE2), 1.5% (LREYSDE3), and 2% (LREYSDE4). The post thawing liquid semen was observed for sperm motility, viability, plasma membrane integrity and acrosome integrity. The result showed that the motility, viability, membrane plasma integrity and acrosomal integrity of spermatozoa in LREYSE extender with 1.5% date extract supplementation (30.44±1.02%; 49.83±0.91%; 43.26±1.02%; and 45.33±0.72% respectively) was significantly higher (P0.05) than others treatment that were 0% (18.21±0.43%; 35.62±0.51%; 30.54±0.60%; and 31.49±0.71% respectively), 0.5% (20.45±0.72%; 40.72±0.87%; 36.81±0.55%; and 38.56±0.63% respectively), 1% (25.68±0.93%; 46.27±0.75%; 40.52±1.02%; and 42.83±1.09% respectively) and 2% (22.55±0.92%; 43,71±0,74%; 38,84±0,71%; and 41,39±0,86% respectively) of date extract supplementation. It is concluded that the 1.5% date extract supplementation in extender can maintain the best post-thawing sperm quality.